Distributed pervasive sensing system for elderly care - Bharti Goel. (2012)
Elderly people require assistance with several daily activities due to age-related decline in physical and mental capabilities. Many of them also need constant monitoring by care givers. Such round the clock manual monitoring is costly as well as labor intensive. There is a need to develop an automatic pervasive sensing system which can monitor the activities of the elderly on a 24-hour basis and provide an appropriate alert to the care givers as soon as it required.